Awareness in the emergency department: A patient's story. (May 2016) - Finlay, Theresa; Parke, Tim
Theresa is a lady with brittle asthma. She presented to the Emergency Department (ED) with an asthma attack and was rapidly intubated and ventilated. From subsequent blood gas results, ventilator pressures and a chest X-ray it soon became clear that she did require ventilation to be continued. The ICU consultant requested she be ventilated until the relaxant wore off and she was subsequently extubated in the ED. Unfortunately she was fully aware for the time she was ventilated. This is her story.